The Consequences of Austerity Policies in Portugal - Caldas, José Castro (2012)
The main characteristics of the Portuguese economy since 2000 are low growth, a rising current account defcit and indebtedness. In the period 2000–2007 Portuguese GDP increased at an annual average rate of 1.4 per cent. The current account defcit, which was 3.5 per cent of GDP in 1995, quickly deteriorated under the EMU to reach 12.5 per cent in 2008. The shift from fscal stimulus to austerity took place in March 2010. In April 2011, assistance was requested from the EU and in the same month a Memorandum of Understanding was negotiated with the troika. Austerity and structural adjustment policies were geared towards reducing the government defcit and debt and rebalancing the current account by cutting wages (»internal devaluation«). The austerity measures adopted since March 2010 are having a strong recessionary impact. Unemployment rates have climbed to unprecedented heights, reaching 15.6 per cent in the frst quarter of 2012. Youth unemployment (15–24) has reached 36.2 per cent. Nominal wages contracted by 3.9 per cent between the third quarter of 2010 and the frst quarter of 2012. As it is becoming clear that austerity will fail to deliver its promises – the defcit is out of control and the public debt keeps growing – clear signs of what the IMF call »reform fatigue« are discernible. However, this discontent tends to take the form, not of the emergence of a political alternative, but rather of the increasing alienation of the public from what it perceives as a corrupt and dishonest political class.